EFEKTIVITAS MEDIA TIKTOK EDUKASI DENGAN PENDEKATAN DEEP LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP - Aura Dela Felisa; Mujahidawati Mujahidawati; Ilham Falani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Mathematical problem-solving ability among junior high school students in Indonesia remains relatively low, while mathematics instruction is generally still dominated by conventional approaches that provide limited opportunities for students to actively construct their understanding. In addition, the use of digital media, particularly TikTok for educational purposes integrated with the Deep Learning approach through the Problem Based Learning (PBL) model, has received limited attention as an alternative instructional strategy to improve students' mathematical problem-solving ability. Therefore, this study aimed to analyze the effectiveness of educational TikTok integrated with the Deep Learning approach through the Problem Based Learning (PBL) model in improving students' mathematical problem-solving ability on the topic of ratio. This study employed a quantitative approach using a Pretest–Posttest Control Group Design involving one experimental class and one control class. Data were collected using a validated essay test and analyzed through descriptive statistics, the Shapiro–Wilk normality test, the Mann–Whitney U test, and N-Gain analysis. The results showed that the implementation of educational TikTok integrated with the Deep Learning approach through the Problem Based Learning (PBL) model produced a significantly greater improvement in students' mathematical problem-solving ability than conventional instruction (p = 0.001). In conclusion, the integration of educational TikTok, the Deep Learning approach, and the PBL model can serve as an effective instructional alternative for enhancing junior high school students' mathematical problem-solving ability. ABSTRAK Kemampuan pemecahan masalah matematis siswa Sekolah Menengah Pertama (SMP) di Indonesia masih tergolong rendah, sementara pembelajaran matematika di sekolah umumnya masih didominasi oleh pendekatan konvensional yang kurang mendorong keterlibatan aktif siswa dalam membangun pemahaman. Di sisi lain, pemanfaatan media digital, khususnya TikTok Edukasi yang diintegrasikan dengan pendekatan Deep Learning melalui model Problem Based Learning (PBL), masih belum banyak dikaji sebagai alternatif pembelajaran untuk meningkatkan kemampuan pemecahan masalah matematis. Oleh karena itu, penelitian ini bertujuan untuk menganalisis efektivitas penggunaan TikTok Edukasi berpendekatan Deep Learning melalui model Problem Based Learning (PBL) terhadap kemampuan pemecahan masalah matematis siswa pada materi rasio. Penelitian ini menggunakan pendekatan kuantitatif dengan desain Pretest-Posttest Control Group Design yang melibatkan satu kelas eksperimen dan satu kelas kontrol. Data dikumpulkan menggunakan tes uraian yang telah divalidasi, kemudian dianalisis melalui statistik deskriptif, uji normalitas Shapiro-Wilk, uji Mann-Whitney U, dan perhitungan N-Gain. Hasil penelitian menunjukkan bahwa penggunaan TikTok Edukasi berpendekatan Deep Learning melalui model Problem Based Learning (PBL) menghasilkan peningkatan kemampuan pemecahan masalah matematis yang secara signifikan lebih tinggi dibandingkan pembelajaran konvensional (p = 0,001). Dengan demikian, integrasi TikTok Edukasi, pendekatan Deep Learning, dan model PBL dapat menjadi alternatif pembelajaran yang efektif untuk meningkatkan kemampuan pemecahan masalah matematis siswa.